'Objects with Objectives': Applied puppetry from practice into theory. Issue 1 (1st July 2020) - Grant, David
This article draws on the dialogue between puppetry and applied drama that arose from the AHRC Objects with Objectives Research Network in 2017–18 to explore a tentative theory of applied puppetry. A range of theoretical approaches to applied drama are examined in the light of practical examples of applied puppetry using case studies from Northern Ireland, South Africa and Australia. Morton (2013) highlights how, in performance 'tension between the material puppet and the imagined puppet' gives rise to a kind of 'double vision' (Tillis 1992), a concept that the article considers alongside Gallagher's (2005) distinction between body image and body schema, Brecht's (1974) V-effekt, Meyerhold's (1998) distinction between the materiality and agency of the actor and Boal's (1992) idea of metaxis. The article concludes that the distancing and conductive qualities of applied puppetry often work in parallel and that the puppet can be seen as the site of metaxis when used in an applied context.